2019
DOI: 10.32725/det.2019.029
|View full text |Cite
|
Sign up to set email alerts
|

Talent Management of Academics: A Systematic Literature Review and Implications for Further Research in Hungary

Abstract: Talent management (TM) has become a key business issue recently, while finding and keeping talents are also crucial in higher education (HE). However, no study summarizes the knowledge on TM of academics. Hence, we conducted a comprehensive systematic literature review searching for existing knowledge about and common processes of TM in HE, and the specialties of TM of academics. We searched for all publications on TM related to academia in Web of Science and Scopus. Non-English and non-article items were excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
1
0
0
2
Order By: Relevance
“…Based on all the answers to RQ1-3, it can be observed that the results of this study are consistent with the process-based TM model by Daruka and Pádár (2019). That model originally adapted Gagné's (2010) process-based approach and the DMGT 2.0 framework to higher education; however, it might be applied in such business circum stances in line with the current findings (Figure 7).…”
Section: Results In Light Of the Process-based Tm Modelsupporting
confidence: 85%
“…Based on all the answers to RQ1-3, it can be observed that the results of this study are consistent with the process-based TM model by Daruka and Pádár (2019). That model originally adapted Gagné's (2010) process-based approach and the DMGT 2.0 framework to higher education; however, it might be applied in such business circum stances in line with the current findings (Figure 7).…”
Section: Results In Light Of the Process-based Tm Modelsupporting
confidence: 85%
“…[3], [10]) szerint a legfrissebb TM-forrásokban felfedezhető valamiféle konszenzus. Ez azonban még mindig nagyon korlátozott mértékű, ezért e cikk célja, hogy egy szisztematikus irodalomkutatás nyomán azonosított, úgynevezett TM-dimenziók [11] gyakorlati megjelenését tesztelje olyan vállalati TM-értelmezéseken, amelyeket egy magyarországi TMfelmérés során adtak a résztvevők. Az eredmények hozzájárulhatnak a TM fogalmának következetesebb használatához, a tématerület szakirodalmának és gyakorlatának fejlődéséhez.…”
Section: Bevezetésunclassified
“…A különböző nézőpontok, megközelítések átfedésén alapulva, a TM legtöbbet idézett forrásainak szisztematikus elemzése során Daruka és Pádár [11] azonosították az alábbi, úgynevezett TM-dimenziókat:…”
unclassified